LIFE SKILLS PROGRAM MANAGEMENT IN IMPROVING ENTREPRENEURSHIP - Maisah; Syukri, Ahmad; Sungkowo (International Journal of Research -GRANTHAALAYAH, 2020)
This Study at Al Baqiyatus Shalihat Islamic Boarding School in West Tanjung Jabung Regency, Karya Pembangunan Al-Hidayah Islamic Boarding School in Jambi City and Al-Munawaroh Boarding School in Merangin Regency Jambi Province. Life Skills Program are a group of skills program that include social skill, personal skill, academic skill and vocational skill. These skills are taught at Islamic boarding schools to equip students to live independently and have Islamic entrepreneurial behavior in the face of the development and progress of the times. The purpose of this study was to determine the management life skills program to improve the behavior of students in entrepreneurship, the excellence of managing life skills program that have been implemented by Islamic Boarding Schools and determined the behavior of students in entrepreneurship. The research approach is used to descriptive qualitative approach. Data collection techniques using observation, interview and documentation. Data analysis using Miles and Huberman models and data validity techniques using data triangulation.